Historical Materialism and Social Evolution
VIII, 244 p.
Keywords: Historical Materialism and Social Evolution brings together a collection of essays which investigate the relationship between Marxist thought and Darwin's theory of evolution by natural selection. Each of the contributors emphasize the idea that the distinctive character of progressive social thought is derived from creative ideas drawn from the study of natural evolutionary processes.